2013
DOI: 10.1007/s00018-013-1506-y
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic control of local translation: the plot thickens with new characters

Abstract: The production of proteins from mRNAs localized at the synapse ultimately controls the strength of synaptic transmission, thereby affecting behavior and cognitive functions. The regulated transcription, processing, and transport of mRNAs provide dynamic control of the dendritic transcriptome, which includes thousands of messengers encoding multiple cellular functions. Translation is locally modulated by synaptic activity through a complex network of RNA-binding proteins (RBPs) and various types of non-coding R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 188 publications
0
29
0
Order By: Relevance
“…NMDAR stimulation globally inhibits dendritic protein synthesis with consequences for translation specificity (reviewed in Thomas et al, 2014). Here, we show that the translational silencing upon exposure to NMDA is linked to the formation of synaptic XRN1-positive bodies, which are novel post-synaptic bodies that contain XRN1 and apparently lack decapping activity and that we termed SX-bodies.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…NMDAR stimulation globally inhibits dendritic protein synthesis with consequences for translation specificity (reviewed in Thomas et al, 2014). Here, we show that the translational silencing upon exposure to NMDA is linked to the formation of synaptic XRN1-positive bodies, which are novel post-synaptic bodies that contain XRN1 and apparently lack decapping activity and that we termed SX-bodies.…”
Section: Discussionmentioning
confidence: 84%
“…RNA molecules might contribute to the stability of RNP liquid droplets by serving as a platform for multiple binding, and we found that RNA breakdown affects SX-body integrity. Additional cohesive forces that might help the condensation of RNP liquid droplets depend on homotypic and heterotypic protein-protein interaction mediated largely by low complexity regions (LCRs) Kato et al, 2012;Brangwynne, 2013;Jonas and Izaurralde, 2013;Thomas et al, 2014). The XRN1 C-terminus displays several LCRs, some of them rich in proline, and we speculate that these LCRs are likely to play a role in SX-body aggregation (Fig.…”
Section: What Is the Nature Of The Sx-bodies?mentioning
confidence: 96%
“…A central regulator for structural plasticity is the enzyme glycogen synthase kinase 3β (GSK3β), which is a target of many psychotropic drugs [8]: Long-term potentiation, which is a functional correlate of synaptic plasticity, leads to inhibition of GSK3β [56, 146], which in turn increases structural plasticity by destabilization and increased turnover of dendritic spines [140]. Furthermore, a host of cytoskeletal proteins [178], as well as local protein translation [197], is required for the proper maintenance and turnover of dendritic spines.
Fig. 1Dendritic spines are remodeled in enriched environment.
…”
Section: Dendritic Spinesmentioning
confidence: 99%
“…These higher-order assemblies of mRNAs and proteins are thought as units for mRNA transport and translational regulation. The molecular mechanisms for mRNA repression during granule movement are partially known and involve several RNA-binding proteins (RBPs; Thomas et al, 2014). Dendritic RNA granules may contain stalled polysomes, thus allowing a fast resuming of protein production (Graber et al, 2013).…”
Section: Introductionmentioning
confidence: 99%